Percepciones estudiantiles sobre la Ética y Filosofía de la Ciencia en el Colegio Científico Costarricense Sede San Carlos - González-Zúñiga, Carlos Rodolfo (2026)
The article describes the development of the research-strengthening activity: “Perceptions on the teaching and learning of ethics and philosophy of science among students of the Colegio Científico de San Carlos.” First, the Ethics and Philosophy of Science course is characterized in terms of its curriculum, and the progress of the research is described through a qualitative methodology of exploratory case analysis. Data collection was carried out using semi-structured interviews, classroom observations, and document analysis. Through a thematic analysis, four themes were established: Notable impressions at the beginning of the course, Teaching and learning processes, Benefits of the course, and Course recommendations. Finally, some preliminary results related to the indicated themes are mentioned, as well as potential implications for the community of scientific high schools in Costa Rica.